The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1183/09031936.03.00095703
|View full text |Cite
|
Sign up to set email alerts
|

A neutrophil elastase inhibitor reduces cigarette smoke-induced remodelling of lung vessels

Abstract: Cigarette smoking produces pulmonary hypertension (PHT) through unknown mechanisms. In animal models acute smoke exposure induces cell proliferation in the small arteries adjacent to the alveolar ducts, and chronic exposure results in muscularisation of these vessels, with changes related to the development of PHT. Studies indicate that serine-elastase inhibitors can prevent experimental monocrotaline-induced PHT. This study examined whether they could also prevent cigarette smoke-induced pulmonary vascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 32 publications
0
18
0
4
Order By: Relevance
“…56,57 Matrix metalloproteinases may also participate in cigarette smoke-induced pulmonary vascular remodeling. 58,59 An interesting potential link between the role of matrix metalloproteinases in smoking-induced emphysema and in smokinginduced vascular disease is cadmium. Cadmium, inhaled in cigarette smoke, induces lung proteolysis.…”
Section: Matrix Metalloproteinases and Vascular Pathophysiology: Focumentioning
confidence: 99%
“…56,57 Matrix metalloproteinases may also participate in cigarette smoke-induced pulmonary vascular remodeling. 58,59 An interesting potential link between the role of matrix metalloproteinases in smoking-induced emphysema and in smokinginduced vascular disease is cadmium. Cadmium, inhaled in cigarette smoke, induces lung proteolysis.…”
Section: Matrix Metalloproteinases and Vascular Pathophysiology: Focumentioning
confidence: 99%
“…Thus, in addition to a genetic predisposition and associated disease, environmental factors may play a pathogenic role. Animal studies have shown that tobacco smoke exposure can lead to pulmonary endothelial dysfunction and plexogenic PH [4,5] , and some reports indicate that this might also be the case in humans [6,7] . In a single-center study, we recently showed a higher prevalence of smokers (former or current) in patients with pulmonary arterial hypertension (PAH) compared to chronic thromboembolic PH (CTEPH) and healthy controls from the Swiss Health Survey (SHS) 2007 [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Desde que as proteinases deixaram de ser consideradas apenas como proteínas de degradação enzimática e tornaram-se importantes moléculas sinalizadoras envolvidas em vários processos biológicos vitais, os inibidores da proteinase estão sendo intensamente investigados (Turk, 2006). Algumas moléculas sintéticas foram desenvolvidas para testar o papel terapêutico dos inibidores de proteinases na DPOC, tais como CP-471,474 (Selman, 2003); ZD0892 (Wright, 2003); SP-B (Guarnieri, 2010); MR889 (Luisetti, 1996); FR901277 (Benetazzo, 1999).…”
Section: Aspectos Fisiopatológicosunclassified